The Stressful Experience of Goal Orientations Under Frustration: Evidence Using Physiological Means - Antoniou, Faye; Alkhadim, Ghadah S. (Frontiers in Psychology, 2022)
The purpose of the present study was to test the hypothesis that goal orientation is associated with divergent forms of emotional reactivity under frustration. Goal orientations were assessed using constructs described in Grant and Dweck (2003), Martin (2006) and Fredricks et al. (2004). Physiological stress levels were measured via a blood volume pulse analysis after individuals were subjected to a computerized Stroop task using a malfunctioning mouse to induce enhanced frustration. The results indicated that performance-avoidance goals were associated with the highest levels of emotional reactivity, with normative outcome goals being significantly more detrimental than ability goals. We concluded that the motivation to avoid failure or to outperform others is the most detrimental determinant of stress and needs to be avoided by all means. Instead, it is suggested that educators emphasize performance using personal best outcomes or by valuing engagement, deep processing and task completion.